2019
DOI: 10.2174/1871530319666190212170140
|View full text |Cite
|
Sign up to set email alerts
|

The Neuromodulatory Effects of ω-3 Fatty Acids and Nano-Curcumin on the COX-2/ iNOS Network in Migraines: A Clinical Trial Study from Gene Expression to Clinical Symptoms

Abstract: Background: Migraine is a common neuroinflammatory disorder characterized by recurrent attacks of pain. Human and experimental models of migraine studies have demonstrated the role played by COX-2/ iNOS in migraine’s neuroinflammatory pathogenesis. COX-2 and iNOS are closely linked and both contribute to inflammation and neurogenic pain in the central nervous system. Omega- 3 fatty acids and curcumin, an active polyphenol of turmeric, have anti-inflammatory and neuroprotective effects through several mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…However, the largest overall prophylactic effect occurred in participants taking the combination of omega-3 fatty acids and curcumin. There was similar treatment efficacy in participants taking either curcumin or omega-3 alone (Abdolahi et al, 2017;Abdolahi et al, 2019). In a similarly-designed study, in addition to prophylactic medications (topiramate and amitriptyline), the effects of either a placebo, curcumin (80 mg daily), coenzyme Q10 CoQ10 are the most widely used components of the coriander plant with the most important constituents being the essential oil and fats (Sahib et al, 2013).…”
Section: Curcumin and Migrainementioning
confidence: 90%
“…However, the largest overall prophylactic effect occurred in participants taking the combination of omega-3 fatty acids and curcumin. There was similar treatment efficacy in participants taking either curcumin or omega-3 alone (Abdolahi et al, 2017;Abdolahi et al, 2019). In a similarly-designed study, in addition to prophylactic medications (topiramate and amitriptyline), the effects of either a placebo, curcumin (80 mg daily), coenzyme Q10 CoQ10 are the most widely used components of the coriander plant with the most important constituents being the essential oil and fats (Sahib et al, 2013).…”
Section: Curcumin and Migrainementioning
confidence: 90%
“…These experiments also confirmed that the combination of omega-3/nano-curcumin significantly reduced the frequency, severity, and duration of headache attacks. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 , 38 ] Human and experimental pre-clinical research also highlighted the role of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS), confirming that they contribute to sustaining inflammation and neurogenic pain in migraine. [ 39 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that magnetic NPs also show 70% chemotherapy (temozolomide)delivering capability and distribution in intracranial tumor region in pet dogs (Young et al, 2018). Moreover, recent studies reveal that treatment with omega-3 fatty acids and curcumin NPs significantly reduces inflammation in migraine patients by suppressing the expressions of TNF-α, intercellular adhesive molecule 1, and cooxygenase-2/inducible nitric oxide synthase (Abdolahi et al, 2017(Abdolahi et al, , 2019Soveyd et al, 2018; Table 1). Together, the above evidences indicate that NPs have enormous potential in brain diseases by facilitating drug delivery, inducing synergistic effects, and reducing drug toxicity.…”
Section: Approved Nanodrugs and Ongoing Clinical Trialsmentioning
confidence: 99%